Predictors of Booster Response to Hepatitis B Vaccine at 15 years of age: A Cross-Sectional School-Based Study - Yu-Sheng Chen; Chia-Hsiang Chu; Jen-Hung Wang; Jun-Song Lin; Yung-Chieh Chang (Pediatrics and Neonatology)
The current consensus does not support the use of booster dose because of its anamnestic response in almost all children 15 years after universal infant hepatitis B virus (HBV) vaccination. However, in our clinical setting, numerous concerned parents request a booster administration for their children. We aimed to provide the possible predictors of booster response in adolescents before this booster administration. Methods: This study comprised a series of cross-sectional serological surveys of HBV markers in 15-year-old individuals between 2008 and 2012. Data on serum hepatitis B surface antigen, hepatitis B surface antibody (anti-HBs), and liver-function biomarkers in a total of 887 senior high-school students were collected. There were two parts to this study: HBV seroepidemiology and booster-response analysis to identify the possible response predictors and decay factors after the HBV booster administration. Results: The overall anti-HBs and hepatitis B surface antigen seropositivity rates were 34.7% and 0.7%, respectively, and the median anti-HBs titer was 3.3 mIU/mL. Six weeks after one dose of recombinant HBV vaccine, the overall booster-response rate in the double-seronegative recipients was 94% (471/501). Among the participants whose initial anti-HBs titers were undetectable or low, 72.4% (247/341) and 95.6% (153/160), respectively, reactivated their anti-HBs titers ≥ 100 mIU/mL about 6 weeks after the booster administration. The likelihood of postbooster anti-HBs titer reaching an adequate protective level increased with the prebooster titer. The female participants had stronger anamnestic responses compared to the male participants. Conclusion: We found that the female participants and prebooster anti-HBs titers above the detection limit of the immunoassay were good predictors of HBV booster response.